2020
DOI: 10.1186/s40360-020-00431-4
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide and spironolactone doses and hyponatremia in patients with heart failure

Abstract: Background: Hyponatremia, a marker of disease severity and prognosis, has been associated with various clinical factors and drug use, especially diuretics. Methods: This observational prospective cohort study enrolled patients hospitalized at the University Hospital Center Split because of heart failure (HF). We investigated the association of clinical variables and cardiovascular drugs, including furosemide, hydrochlorothiazide, spironolactone, and their doses, with the presence of hyponatremia at admission. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
0
8
1
2
Order By: Relevance
“…Hyponatremia is considered to be one of the important causes of poor prognosis in patients with heart failure [ 28 ], and thus prevention of its onset is important. FUR has been reported to cause hyponatremia in a dose-dependent manner [ 29 ], and unfortunately, the serum sodium concentration was significantly decreased by increasing the dose of FUR in this study as well. On the other hand, with the addition of TLV, which is a water diuretic, mild elevation of serum sodium was observed in patients with a tendency toward hyponatremia.…”
Section: Discussioncontrasting
confidence: 52%
“…Hyponatremia is considered to be one of the important causes of poor prognosis in patients with heart failure [ 28 ], and thus prevention of its onset is important. FUR has been reported to cause hyponatremia in a dose-dependent manner [ 29 ], and unfortunately, the serum sodium concentration was significantly decreased by increasing the dose of FUR in this study as well. On the other hand, with the addition of TLV, which is a water diuretic, mild elevation of serum sodium was observed in patients with a tendency toward hyponatremia.…”
Section: Discussioncontrasting
confidence: 52%
“…Several clinical conditions and cardiovascular risk factors, such as diabetes mellitus, chronic obstructive pulmonary disease, and alcohol consumption may also be associated with hyponatremia. A similar study by Velat Ivan et al 6 reveals that high doses of furosemide and spironolactone, or concomitant use of these diuretics, seem to be an important cause of hyponatremia in HF patients, particularly in combination with advanced age, diabetes, and alcohol consumption. Diuretic dose reduction may help to avoid hyponatremia and improve clinical status and prognosis in such patients.…”
Section: Complicationsmentioning
confidence: 70%
“…Kiliçkiran Avci et al reported that LVEF is lower in hyponatremic HF group of patients than in normonatremic one ( p ≤ 0.002) [ 23 ]. In another study, published by Velat et al, it was identified that among HF patients with LVEF ≤ 45% hyponatremia was present in 48.1% of them, while normal serum natremia was present in 37.7% ( p = 0.02) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study performed by Velat et al, NT-proBNP levels, marker of HF severity, were significantly higher in hyponatremic than in nonhyponatremic HF patients ( p = 0.006). Levels of NT-proBNP levels presented inverse significantly correlations with the glomerular filtration rate and LVEF [ 24 ].…”
Section: Discussionmentioning
confidence: 99%